Translingual crossings: an enactive-performative approach to a pedagogical guide for the teaching of Portuguese as a welcoming language to children - dos Santos Abreu, Marcella [UNESP]; Rocha, Cláudia Hilsdorf (My University, 2024)
This article revisits the jongo activity ‘Pisei na Pedra’ (2014) integrated into the Nossa Casinha guide (Martins & Sala, 2022) for teaching Portuguese to migrant children. Jongo is seen as an Afro-Brazilian form of expression, encompassing chants, drumming, collective dance, and spirituality (Rufino, 2014, 2023). The connection between this assembly (Pennycook, 2018) and an enactive-performative pedagogy, uniting biological and aesthetic aspects of poetic languages (Aden & Eschenauer, 2020; Maturana & Varela, 1987; Lecoq, 1997, cited in Aden & Eschenauer, 2020), forms a translingual framework. This allows jongo to be understood as an Afro-diasporic expression in anti-racist education. This perspective also affirms the aesthetic, emergent, experiential, embodied, and transformative nature of jongo as a decolonial practice. By challenging the conservative approach of language activities favoring compartmentalization, assimilation, and monolingualism, the translingual framework promotes transformative education in Portuguese as an additional language. It embraces complexity, relationality, and affectivity as integral to our experiences in linguistic education.